Development of ductile concrete for visual sensor enabled 3D-printing - Lim, Rae-Anne Ying (Nanyang Technological University, 2024)
This report consists of five chapters in total. The first is the introduction, where the explanation for the need to develop a ductile cementitious material that is suitable for 3D printing for use in building and construction is explained. This project focused on using polymer fibre reinforcements in the develop of the material. It aims to evaluate the suitability for the material in regards to 3D printing as well as evaluate the impact of fibre types and fibre lengths on the performance of the material. This is followed by the objective and scope of the study. In the second section, the literature review detailed previous studies done in relation to the topic of the project, such as reviewing additive manufacturing (AM) and the difference between polyvinyl alcohol (PVA) and polyethylene (PE) fibre. This section will give a clearer scope as well as better understanding of the material used in the development of the material. The third section is on the experimental materials and methods. It outlines the materials and mix designs that were experimented, the equipment used and experimental procedure, as well as the tests conducted on the samples. For the fourth section, the data and observations obtained from the concrete mixing and tests conducted were calculated, summarised, and analysed. The results did not show definitive conclusions. Last but not least, section five evaluates the results and indicates gaps in the project that can be improved on for future research.